2017
DOI: 10.1038/ncomms15362
|View full text |Cite
|
Sign up to set email alerts
|

Thermogenetic neurostimulation with single-cell resolution

Abstract: Thermogenetics is a promising innovative neurostimulation technique, which enables robust activation of neurons using thermosensitive transient receptor potential (TRP) cation channels. Broader application of this approach in neuroscience is, however, hindered by a limited variety of suitable ion channels, and by low spatial and temporal resolution of neuronal activation when TRP channels are activated by ambient temperature variations or chemical agonists. Here, we demonstrate rapid, robust and reproducible r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 64 publications
0
44
1
Order By: Relevance
“…Direct thermal activation of TRPA1 is unlikely, as its debated thermal activation is prominently for cold stimuli rather than warm 7,36 . A recent work suggested a direct activation of TRPA1 by transient heat induced by ultrafast infrared laser pulse,51 but the temperature‐time dynamics explored were quite different from those explored in this study. Interestingly, a recent study reported the implication of TRPA1 in osmotic‐induced Ca 2+ influx 52 .…”
Section: Resultscontrasting
confidence: 62%
“…Direct thermal activation of TRPA1 is unlikely, as its debated thermal activation is prominently for cold stimuli rather than warm 7,36 . A recent work suggested a direct activation of TRPA1 by transient heat induced by ultrafast infrared laser pulse,51 but the temperature‐time dynamics explored were quite different from those explored in this study. Interestingly, a recent study reported the implication of TRPA1 in osmotic‐induced Ca 2+ influx 52 .…”
Section: Resultscontrasting
confidence: 62%
“…Similar to its predecessors, thermogenetics permits controlled activation or inhibition of neuronal activity using thermal stimulus (Bernstein et al, 2012). Molecules with inhibitory effects, e.g., Drosophila melanogaster dynamin GTPase (Kitamoto, 2001) and excitatory effects from the thermoTRP family (Dhaka et al, 2006), e.g., Drosophila melanogaster TRPA1 (Viswanath et al, 2003;Hamada et al, 2008), rat TRPM8 (Peier et al, 2002;Peabody et al, 2009) and snake TRPA1 (Ermakova et al, 2017), have been discovered. Studies have demonstrated a successful thermal-induced neural activity modulation in drosophila, zebra fish and mouse cultured neurons, but no evidence in in vivo models have been reported (Bath et al, 2014;Ermakova et al, 2017).…”
Section: In Vivo Modulation Of Vagal Afferent Activitymentioning
confidence: 99%
“…Our model is extendable to other brain regions or biological preparations differing in scattering properties, thus offering a unique and flexible tool for the design of complex optogenetics experiments with minimal sample heating. It will surely prove useful also to simulate the temperature distribution under different excitation configurations (including single-and threephoton excitation) and imaging geometries (e.g., light sheet microscopy, stimulated emission depletion microscopy, or Bessel beam illumination) or to optimize light distribution and illumination conditions for thermogenetic experiments (Bernstein et al, 2012;Ermakova et al, 2017;Hamada et al, 2008).…”
Section: Simulated Temperature Rise and Experimental Electrophysiolmentioning
confidence: 99%